A Combined Transcriptomic and Proteomic Approach to Reveal the Effect of Mogroside V on OVA-Induced Pulmonary Inflammation in Mice - Dou, Tong; Wang, Juan; Liu, Yisa; Jia, Jiangang; Zhou, Luwei; Liu, Guoxiang; Li, Xiaojuan; Han, Mengjie; Lin, Jiaxun; Huang, Fengxiang; Chen, Xu (Frontiers in Immunology, 2022)
Mogroside V, a bioactive ingredient extracted from natural function food Siraitia grosvnorii which possess moistening lung and relieving cough activities, but its underlying mechanisms were rarely studied. To estimate its potential protective effect on OVA-induced pulmonary inflammation and understand its system-wide mechanism, an integrated omics was applied in this study. Mogroside V effectively reduced the levels of IgE, TNF-α and IL-5 in OVA-induced mice. The results of RNA-seq and DIA (Data independent acquisition) proteomics approach revealed that 944 genes and 341 proteins were differentially expressed in the normal control group (NC) and ovalbumin-induced control group (OC), 449 genes and 259 proteins were differentially expressed between the OC and the 50 mg/kg mogroside V group (MV). After combined analysis of the transcriptome and proteome, 93 major pathways were screened. And we discovered that mogroside V exert anti-inflammation effect in lung via NF-κB and JAK-STAT the two signaling pathway among the pathway mentioned above. In addition, we found that the key regulatory molecules (Igha, Ighg1, NF-κB, Jak1 and Stat1) in the two pathway activated in inflammation and inhibited by mogroside V. And mogroside V may be the main bioactivity component to exert lung moistening and cough relieving effects in Siraitia grosvenorii.